2020
DOI: 10.1002/mabi.202000248
|View full text |Cite
|
Sign up to set email alerts
|

S‐Nitrosoglutathione‐Based Nitric Oxide‐Releasing Nanofibers Exhibit Dual Antimicrobial and Antithrombotic Activity for Biomedical Applications

Abstract: The novel use of nanofibers as a physical barrier between blood and medical devices has allowed for modifiable, innovative surface coatings on devices ordinarily plagued by thrombosis, delayed healing, and chronic infection. In this study, the nitric oxide (NO) donor S‐nitrosoglutathione (GSNO) is blended with the biodegradable polymers polyhydroxybutyrate (PHB) and polylactic acid (PLA) for the fabrication of hemocompatible, antibacterial nanofibers tailored for blood‐contacting applications. Stress/strain be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 81 publications
1
31
0
Order By: Relevance
“…The current pipeline for new antibiotics is drying, which is even more vexatious for healthcare professionals. Currently, clinicians and researchers are forced to look for alternative agents to antibiotics, including bacteriophages and their lysins, antibacterial metal nanoparticles, phytochemicals, antimicrobial peptides, nitric oxide, and other secondary metabolites [36][37][38][39][40][41]. Lysins have gained much popularity because of their high bactericidal properties, rapid killing activity, low risk of resistance, and modular proteinaceous structure.…”
Section: Discussionmentioning
confidence: 99%
“…The current pipeline for new antibiotics is drying, which is even more vexatious for healthcare professionals. Currently, clinicians and researchers are forced to look for alternative agents to antibiotics, including bacteriophages and their lysins, antibacterial metal nanoparticles, phytochemicals, antimicrobial peptides, nitric oxide, and other secondary metabolites [36][37][38][39][40][41]. Lysins have gained much popularity because of their high bactericidal properties, rapid killing activity, low risk of resistance, and modular proteinaceous structure.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the incorporation of nitric oxide (NO) donor S-nitrosoglutathione (GSNO) onto PHB/PLA nanofibers exhibited dual antibacterial and anti-thrombotic activity [ 100 ]. The NO released from nanofibers was effective in reducing the number of attached S. aureus cells and platelet adhesion by approximately 80% and 65%, respectively [ 100 ]. Li et al developed a stimuli-triggered biocide-loaded PHA-based nanofiber with a core-shell structure [ 101 ].…”
Section: Applications Of Pha Nanocarriersmentioning
confidence: 99%
“…And natural biopolyester materials can make drugs achieve controllable release in time and space, improving the bioavailability of drugs and do not need frequent administration, and can maintain the effective concentration of drugs in vivo for a long time. Furthermore, the selection of EPS materials is very flexible, so many drugs (antisepsis and anti-inflammation, 118,[120][121][122][123][124][125][126] chemotherapy drugs, 127 and others 129,130 ) can be added to the appropriate solution for EPS (Table 5). Analysis of the literature on EPS of natural bio-polyester materials for drug release has been found in recent 10 years, and found that the research and development of drug release are particularly active in the last 5 years.…”
Section: Drug Delivery From Pha Nanofibersmentioning
confidence: 99%